Effect of particle size variations of gypsum bonded investment powders on metallurgical quality of investment castings - Yaman, B.; Cigdem, M. (TAYLOR & FRANCIS LTD, 2010)
In the present work, the effect of particle size distribution parameters of investment powder on the metallurgical characteristics of castings produced by flask mould investment casting process was investigated. The main aim of this study is to establish the relationships between the casting quality and investment powder characteristics. For this purpose, models for tensile, density and surface roughness specimens were prepared in accordance with the standards and these models were moulded by gypsum bonded investment powders. Specimens of sterling silver (92.5Ag-7.5Cu alloy) were subsequently cast into these moulds by centrifugal casting process. After the completion of solidification process, the specimens were tested and results were analysed. The preliminary results illustrate that fineness of investment powders play an important role in determining the metallurgical quality of castings produced by investment casting process.
Keywords: Investment powders; Jewellery castings; Dental and body implants; Metallurgy & Metallurgical Engineering